HUGC - MS ANALYSIS OF LEAF AND STEM BARK OF CLEIDION NITIDUM (MUELL. – ARG.) THW. EX KURZ. (EUPHORBIACEAE) - Das N, Mohan; Sundari S, Sivakama; S, Karuppusamy; VR, Mohan; PARTHIPAN B (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: GC-MS (Gas chromatography and mass spectroscopy) analysis of ethanol extracts of leaf and stem bark of Cleidion nitidum was carried out to detect the bioactive components. Methods: Â The chemical compositions of the ethanolic extract of leaves and bark of Cleidion nitidum were investigated using Perkin â€“ Elmer Gas Chromatography â€“ Mass Spectra while mass spectra of the compounds found in the extract was matched with the National Institute of Standards of Technology (NIST) library. Â Results: Â Gas chromatography mass spectra (GC-MS) analysis revealed the presence of 16 compounds from leaves and 5 compounds from bark of the Cledion nitidum were identified. In GC-MS analysis , some of the phytocomponents screened were squalene, 3, 7, 11, 15-Tetramethyl-2, hexadecen-1-ol , Phytol and Vitamin E in leaves whereas, Thiophene-3-carbonitrite tetrahydro-4-oxo-, Dimethyl-2,6,10-dodecatrien-1-ol , D-Mannotetradecane-1,2,3,4,5-pentaol and Octanal 7-methoxy-3-7-dimethyl (5.13%) major compounds in the bark extract. Â Conclusion: These results indicate the ethanol extract of leaf and stem bark of Cleidion nitidum possesses potent anti-tumor, anticancer, cancer preventive, anti-inflammatory antioxidant, antibacterial and pesticide effects so that it can be recommended as a plant of phytopharmaceutical importance. Keywords: Cleidion nitidum, GC-MS, Squalene, Phytol, vitamin-E and various applications